The role of immigrant organisation in the community life - Serbs in Chicago - Pavlović Mirjana P. (Glasnik Etnografskog Instituta SANU, 2002)
Immigrant organisations decisively influenced the gathering of Serbs in Chicago and the forming of their ethnic community. These organisations also contributed to the preservation of their ethnic identity. Apart from that, they influenced the forming of the specific culture of American Serbs, as well as the affirmation of the immigrants in the wider American society.